Cerebral hemodynamics among non-diabetic hemodialysis patients - Maha Abdelmoneim Behairy; Ahmed ElSadek; Mahmoud Sadek; Abdelbassit El Shaarawy (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery, 2019)
Abstract Background Cerebrovascular accidents and cognitive impairment is a frequent complication of end-stage renal disease (ESRD) on regular hemodialysis (HD). Objective To evaluate cerebral circulation hemodynamics in non-diabetic prevalent hemodialysis patients by transcranial Doppler (TCD). Patients and methods The cross-sectional study included 50 ESRD patients on regular hemodialysis > 6 months in Ain Shams University Hospitals, Cairo, Egypt. Diabetic patients; chronic liver disease patients Child-Pugh class B or C; smokers; history of evident of cardiac, peripheral, or cerebrovascular insult; uncontrolled hypertension; anemia; collagen disease; and active infection were excluded from the study. An assessment of cerebral circulation hemodynamics by TCD in non-dialysis day to examine mean flow velocity (MFV) in the middle cerebral artery (MCA) and posterior cerebral artery (PCA). Results An assessment of cerebral circulation hemodynamics revealed that 16 (32%) of the patients showed decrease MFV in MCA and 30 (60%) were normal. Regarding MFVs in PCA, 13 (26%) of the patients showed decrease MFVs, 33 (66%) were normal, and 4 (8%) of the patients failed due to poor bone window, significant reduction of MCV and PCA velocities in HD with urea reduction ratio < 65%, and a significantly negative correlation of MFV, PCA, and hemoglobin level (P < 0.05). Conclusion There is a high frequency rate of decreased MCA and PCA MFV (32%, 28%), respectively, among non-diabetic prevalent hemodialysis patients with significant correlation to hemodialysis adequacy.